EKSPERIMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE (TPS) DAN TWO STAY-TWO STRAY (TS-TS) PADA POKOK BAHASAN PERSAMAAN DAN PERTIDAKSAMAAN KUADRAT DITINJAU DARI GAYA BELAJAR PADA SISWA SMA NEGERI KELAS X DI KABUPATEN PONOROGO - Fuany, Anggun; Budiyono, Budiyono; Usodo, Budi (Jurnal Pembelajaran Matematika, 2016)
Abstract. The objectives of this research were to determine: (1) which students had the better mathematics learning achievement, instructed with TPS, TS-TS, or direct learning; (2) which students had the better mathematics learning achievement, those with the converger, diverger, assimilator, or accommodator learning style; (3) in each learning style, which students had better mathematics learning achievement, instructed with TPS, TS-TS, or direct learning; (4) in each learning model, which students had a better mathematics learning achievement, those with the converger, diverger, assimilator, or accommodator learning style. This study was aquasi-experimental study with 3 x 4 factorial designs. The study population was a tenth grade student of State SMA in Ponorogo in academic year of 2015/2016. Sampling was done by stratified cluster random sampling technique. The study sample consisted of students in 3 schools namely SMA Negeri 1 Badegan, SMA Negeri 1 Kauman, and SMA Negeri 1 Bungkal with a sample size of 226 students. Data analysis used unbalanced two-way ANAVA with a significance level of 5%. The results of the research are as follows. (1) The students instructed with TPS had learning achievement as good as TS-TS, those with TPS had learning achievement better than those with direct learning, while those TS-TS had learning achievement as good as those with direct learning. (2)The students with the converger learning style had learning achievement better than those with the diverger and assimilator learning style, the students with the converger learning style had learning achievement as good as those with the accommodator learning style, the students with the diverger, assimilator, and accommodator learning style had a same learning achievement. (3) In each learning style, the students mathematics learning achievement was in consistency with the result (1); (4) In each learning model, the students mathematics learning achievement was in consistency with the result (2).Keywords: TPS, TS-TS, Direct Learning, learning styles, and learning achievement